Drug-related perinatal damage from the pharmacological point of view - Laura Cuzzolin (Hygeia Press di Corridori Marinella, 2014)
Medications prescribed to the mother during pregnancy make the foetus vulnerable to adverse effects and the same vulnerability is evident in the phase of adaptation to extrauterine life, particularly delicate in preterm newborns. Among different tissues, the liver and the kidney are particularly sensitive to drugs essentially because they are physiologically immature at birth and have an important role in regulating the effects of medicines inside the body with their primary detoxifying functions. In this minireview hepatic and renal risks related to prenatal and postnatal exposure to paracetamol and NSAIDs have been examined, being these drugs frequently used during pregnancy and in the neonate for their analgesic/antipyretic effects. Moreover, from an analysis of the literature several case reports of neonatal poisoning deriving from transplacentally-acquired overdoses or administration in the first period of life have been reported.   Proceedings of the International Course on Perinatal Pathology (part of the 10th International Workshop on Neonatology · October 22nd-25th, 2014) · Cagliari (Italy) · October 25th, 2014 · The role of the clinical pathological dialogue in problem solving Guest Editors: Gavino Faa, Vassilios Fanos, Peter Van Eyken